“Perspective of Ischemic Heart Disease (Iqfari Marad-i-Qalb) with reference to Unani Medicine” - Eram, Faseeha; Quamri, Mohammad Aleemuddin; Ahmad Bhat, Muzafar Din; Siddiqui, Uzma; Nida, Sumbul (Bangladesh Journal of Medical Science, 2023)
Background: Ischemic heart disease (IHD) also known as coronary artery disease (CAD) is the leading cause of death worldwide. IHD is caused by obstruction of one or more coronary arteries. Among the various causes of obstruction atherosclerosis is the leading cause. Physical inactivity, smoking, saturated fat rich diet, hypertension, diabetes mellitus, dyslipidaemia are modifiable risk factors for atherosclerosis which ultimately results in IHD. In this article we will discuss the disease in the light of Unani system of Medicine and how to manage it depending on the understood concepts Methods: A number of classical Unani textbooks were referred for description of various heart diseases and various search engines such as PubMed, Google Scholar and Research Gate were cited for recent advancements using the key words IHD, atherosclerosis, cardio-protective herbal drugs, etc. Conclusion: Owing to the irreversible damage due to IHD it is better to prevent myocardium damage by minimising the risk factors at its earliest. In Unani system of medicine many cardio-protective drugs have been described which when combined with lifestyle modification can play vital role in keeping cardiac diseases at bay. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 475-481